Madura Halal Tourism Village Destinations: Strategy for Tourism Market Competitiveness and Loyalty after the Covid 19 Pandemic - Faidal (Journal of Islamic Economics Perspectives, 2022)
Abstract In an increasingly saturated market, the fundamental task of tourism village destination management is to understand how the competitiveness of tourist village destinations can be improved and maintained. Thus there is a strong need to identify and explore competitive advantages and to analyze the actual competitive position (Gomezelj, Mihalji?, 2008). Identifying competitors and determining the destination's advantages and disadvantages relative to competitors is an integral part of successful halal tourism destination marketing management. The purpose of this research is to conceptualize the competitiveness of Madura halal tourism village destinations, formulate strategies to manage halal tourism village destinations effectively to help management make policies and for practitioners to better understand the advantages and problems of halal tourism village destinations and the development of halal tourism in Madura. especially after the COVID-19 pandemic. Methods This research uses a mix method with triangulation (case study design and survey design). For qualitative, data were collected from a number of tourist village destinations through observation, in-depth interviews, and FGD methods. The competitiveness of Madura as a halal tourism village destination is based on 7 sub-variables including: tourist attractions, most of the respondents tend to state that they are in good condition. also seen from the aspect of accessibility, amenities and institutions, that overall, respondents tend to say they are ready. The accommodations available in Madura as a whole have implemented the halal principle in their services. need commitment and consistency in working on halal tourism in Madura in order to be competitive with other tours.